Consumers' adverse drug event reporting via community pharmacists: three stakeholder perception - Tanattha Kitisopee; Jirunya Assanee; Bernard A. Sorofman; Suntaree Watcharadmrongkun (Taylor & Francis Group, 2022)
Background Adverse drug event (ADE) reporting is a significant process to increase consumer care and consumer safety associated with the use of medicines. An in-depth investigation into low ADE reporting by consumers and community pharmacists was undertaken to uncover interventions to improve reporting. Method In-depth interviewing of the three parties; consumers, pharmacists and employees of the Pharmacovigilance Center in Thailand, was used to collect the data. They were interviewed about ADE reporting experiences and contributing factors and problems of ADE reporting. Thematic analysis was used to interpret the results. Result The HPVC received few ADE reports from consumers. Most community pharmacists received ADE reports from consumers; however, the Pharmacovigilance Center received few ADE reports from community pharmacists. ADE reporting of community pharmacists and consumers were influenced by many factors which were categorized into four themes which were (1) "Cognition" (awareness, attitude and responsibility); (2) "Reporting process" (complication, competency, information deficiency, feedback, and resource); (3) "Inducer" (service orientation, acquaintanceship, motivation, severity level, regulatory and reward); and (4) "Obstacle" (doubt, belief and prosecution). Conclusion Health professionals should motivate consumers to report ADEs. Building social responsibility and benefits and increasing knowledge of reporting process, channels, and system to both community pharmacists and consumers were recommended. Providing rewards and making community pharmacists feel comfortable to report ADEs by simplifying the ADE form and providing training, guidelines, and an ADR assessment tool can drive them to report ADEs. Feedback to consumers by confirming whether it was ADE and feedback to pharmacists that the Pharmacovigilance Center received their reports and their reports were utilized were also important.